Leishmaniasis Chemotherapy-Challenges and Opportunities - Croft, S. L. (2012)
Clin Microbiol Infect 2011; 17: 1478-1483 ABSTRACT: Although there have been significant advances in the treatment of visceral leishmaniasis (VL), there remain challenges to ensure that treatments effective in India are also effective in other regions of the world and to identify treatment for post kala-azar dermal leishmaniasis as well as the opportunity to develop a safe oral short-course treatment. At the same time, there have been few advances for the treatment of simple or complex forms of cutaneous leishmaniasis (CL), other than topical paromomycin formulations. The main challenge for CL is to ensure that this disease is on the research and development agenda, so that new drugs are evaluated or compounds are screened in appropriate models, and that the standardization of quality of clinical trials is guaranteed. Problems also remain in the treatment of HIV/leishmaniasis co-infected patients. We are some way from having the ideal treatments for VL and CL and drug research and development for these diseases must remain focused.